Context specificity of Atlantic spotted dolphin acoustic signals in the Canary Islands. Issue 4 (4th July 2017) - Papale, Elena; Perez-Gil, Monica; Castrillon, Juliana; Perez-Gil, Enrique; Ruiz, Leire; Servidio, Antonella; Tejedor, Marisa; Giacoma, Cristina; Martín, Vidal
Abstract : The behavioural context provides opportunities for studying the use and characteristics of acoustic signals. We analysed the context-specific use of acoustic signals in a population of Atlantic spotted dolphins around the Canary archipelago. We calculated the whistle diversity, the mean value of whistle stereotypy and the repetition rate of both tonal and burst-pulsed sounds. Eleven parameters of frequency, signal duration and modulation were measured from each whistle. Results showed that whistle diversity and whistle and chirp repetition rates were negatively correlated with group size, but only whistle diversity and the mean number of stereotypy were related to behavioural activity. Whistles were more complexly modulated during high behavioural activity than when engaged in moderate movements. Furthermore, during socialising and feeding, the highest mean value of stereotypy was displayed, and the parameters of non-stereotyped whistles had lower variability. Our results suggest the use of a complex communication system to improve the efficiency of communication through context-specific signal combinations, the usage of different signals and their modulation pattern. Our study produces evidence to support the hypothesis that acoustic plasticity and differences in call characteristics may be indicative of behavioural and social acoustic environment.